Survival in melanoma in the nordic countries into the era of targeted and immunological therapies - Tichanek, Filip; Försti, Asta; Hemminki, Akseli; Hemminki, Otto; Hemminki, Kari (European journal of cancer (Oxford, England, 2023)
OBJECTIVES: Survival in melanoma has been increasing and the most recent interest is to observe the population-level impact of novel targeted therapies and immunotherapy. We analysed survival in melanoma from Denmark (DK), Finland (FI), Norway (NO) and Sweden (SE) over a 50-years period (1971-2020). METHODS: Relative 1-5/1- and 5-year survival data were obtained from the NORDCAN database for the years 1971-2020. We estimated annual changes in survival rates and determined significant breaking points for trends. RESULTS: Survival in melanoma has reached the point where 1-year survival is approaching 100% (men 97.5-98.6%, women 98.4-99.3%, depending on the country) and 5-year survival is 93% for men (91.5-95.2%) and 96% for women (95.3-97.2%). The highest survival figures were for DK. Significant increases in both 1- and 5-year survival were observed in most countries even towards the end of the follow-up (from 2006 to 2010-2011-2015 and further to 2016-2020). CONCLUSIONS: The main increase in melanoma survival took place up to year 1990, which was probably largely achieved through successful population campaigns for sun protection and programmes for early detection of lesions. Survival increased again after year 2000 up to the last period 2016-2020. This late development coincided with the introduction of targeted therapies using BRAF and BRAF/MEK inhibitors, and towards the end of the time period availability of checkpoint inhibitors. The success of melanoma treatment in DK was mostly likely due to the efficient use of modern therapies and to the centralised treatment for metastatic disease.
Keywords: Skandinávie a severské státy; imunoterapie; protoonkogenní proteiny B-Raf; Sun protection; Male; Melanoma; lidé; Humans; míra přežití; Proto-Oncogene Proteins B-raf; Conditional survival; Targeted therapy; Survival Rate; Relative survival; melanom; mužské pohlaví; ženské pohlaví; Female; Scandinavian and Nordic Countries; Immunotherapy